PENERAPAN EDUGAME INTERAKTIF UNTUK PENGENALAN PAKAIAN ADAT NASIONAL INDONESIA - Nugraheny, Dwi; Destiranti, Ayuningtias (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Interactive Edugame is an educational media are widely used in today, with interesting visualization, so that the public easily identify the information submitted. Interactive Edugame introduction o f the National Indigenous Apparel Indonesia can be a medium of learning and creativity, so that is making user easier to understand the National Indigenous Apparel. Interactive Edugame developed using Adobe Flash and action script programming language. The results already obtained from tests using questionnaires and calculated the Likert method is 74.1 percent, it can be concluded that the application interactive edugame introduction o f the National Indigenous Apparel Indonesia entered good criteria.